2013
DOI: 10.1007/s00127-013-0759-y
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and symptoms among American Indians and Alaska Natives: a review of the literature

Abstract: Purpose: American Indians and Alaska Natives (AI/ANs) experience high rates of trauma and posttraumatic stress disorder (PTSD). We reviewed existing literature to address three interrelated questions: 1) What is the prevalence of PTSD and PTSD symptoms among AI/ANs? 2) What are the inciting events, risk factors, and comorbidities in AI/ANs, and do they differ from those in the general U.S. population? 3) Are studies available to inform clinicians about the course and treatment of PTSD in this population? Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 67 publications
3
46
0
Order By: Relevance
“…Importantly, posttraumatic stress disorder (PTSD) was not assessed in the Wave 1 NESARC data analyzed here. Other studies have shown elevated rates of trauma and ensuing PTSD among AIANs [55, 57, 66, 68, 71] compared to other Americans. Finally, treatment-seeking measures were limited by the non-inclusion of traditional healers, who are frequent sources of care in AIAN communities [26], and the lack of assessment of duration or quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, posttraumatic stress disorder (PTSD) was not assessed in the Wave 1 NESARC data analyzed here. Other studies have shown elevated rates of trauma and ensuing PTSD among AIANs [55, 57, 66, 68, 71] compared to other Americans. Finally, treatment-seeking measures were limited by the non-inclusion of traditional healers, who are frequent sources of care in AIAN communities [26], and the lack of assessment of duration or quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Students and teachers who published accounts of their boarding school experiences were exceptional. Many of their descriptions recount harsh discipline and students running away from school in freezing weather; their suffering sometimes led to post-traumatic stress syndrome (Bassett, Buchwald, & Manson, 2014;Lajimodiere, 2014). However, some students found boarding schools a refuge from poverty at home and a place to make friends and learn useful skills (Child, 1998;Lomawaima, 1994;McBeth, 1983).…”
Section: Institutional Lifementioning
confidence: 99%
“…2224 Since the frequency of traumatic events is significantly elevated, there is an increased likelihood that an AI/AN individual will experience multiple traumas compared to national samples. 21,2528 …”
Section: Introductionmentioning
confidence: 99%